In Vitro Evaluation of Portuguese Propolis and Floral Sources for Antiprotozoal, Antibacterial and Antifungal Activity - Soraia I Falcao (2014)
Propolis is a beehive product with a very complex chemical composition, used since ancient times in several therapeutic treatments. As a contribution to the improvement of drugs against several tropical diseases caused by protozoa, we screened Portuguese propolis and its potential floral sources Populus x Canadensis and Cistus ladanifer against Plasmodium falciparum, Leishmania infantum, Trypanosoma brucei and Trypanosoma cruzi. The toxicity against MRC-5 fibroblast cells was evaluated to assess selectivity. The in vitro assays were performed following the recommendations of WHO Special Programme for Research and Training in Tropical Diseases (TDR) and revealed moderate activity, with the propolis extracts presenting the relatively highest inhibitory effect against T. brucei. Additionally, the antimicrobial activity against Staphylococcus aureus, Candida albicans, Trichophyton rubrum and Aspergillus fumigatus was also verified with the better results observed against T. rubrum. The quality of the extracts was controlled by evaluating the phenolic content and antioxidant activity. The observed biological activity variations are associated with the variable chemical composition of the propolis and the potential floral sources under study. Copyright (c) 2013 John Wiley & Sons, Ltd.